Terminal velocity of spheres in water. (12th August 2020) - Cross, Rod
Abstract: A standard physics experiment for students is to measure the terminal velocity of an object in air or in glycerine. A more difficult challenge is to measure the terminal velocity in water since the depth of the water needs to be large or the object needs to be dropped in the water at a speed close to its terminal velocity. Results obtained by filming the fall in a fish tank are presented for a range of different spheres, showing how the terminal velocity depends on the density of the sphere and its radius. The results provide a useful measurement of the drag force and the drag coefficient for a sphere in water. An additional experiment to measure the Magnus force is described where a ball was spinning when it entered the water.